DNA barcoding de Platanichthys platana (Regan, 1917) (Clupeiformes, Clupeidae) de diferentes bacias hidrográficas. - Ramos, Laura Ivana (2022)
South America has fish endemic to continental fresh waters, but derived from clades predominantly and ancestrally distributed in marine environments, such as Platanichthys platana. This species is considered the smallest sardine of the Clupeidae with its type locality in the La Plata river. In 2007, there were the first records of P. platana in the upper Paraná river basin and in 2012 in the upper Paraná river floodplain. The variation in the length of specimens from this basin generated curiosity about their identity and origin of introduction. Sequences from the COI region of the specimens were used for genetic distance calculations, construction of gene trees and haplotype networks. The results obtained indicate that all analyzed specimens belong to P. platana. Eight haplotypes were found, some exclusive to the coastal basins of Santa Catarina, Rio Grande do Sul and Negro river basin. The basins of the La Plata river, the Lago and the upper Paraná river floodplain shared different haplotypes. The phylogeographic pattern presented in this study can be justified by the presence of populations of P. platana in the same paleoarea, before the geological process that configured the current architectures of the observed basins, by vicariance. During the Mesozoic and Cenozoic several vicarious events occurred between the coastal watersheds of Brazil that can be attributed to marine regressions and transgressions by continental lands. It is also assumed that specimens from the upper Paraná river floodplain were introduced to the region from Argentine regions.